2008
DOI: 10.1177/0363546507311603
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Capsular Area in Patients with Anterior, Posterior, and Multidirectional Shoulder Instability

Abstract: Our results reinforce the concept that capsular elongation and laxity, either preexisting or acquired, play a role in certain instability conditions of the shoulder. Additional work is needed to determine how to correlate surgical decision making with the cross-sectional area measurements demonstrated in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 49 publications
0
58
1
Order By: Relevance
“…Because an injected dye distends the capsule, MRAs have been used as a tool to identify patulous capsules in shoulder instability [7,12,15,21,28]. To date, however, the utility of the MRA as a tool to detect patulous hip capsules is unclear.…”
mentioning
confidence: 99%
“…Because an injected dye distends the capsule, MRAs have been used as a tool to identify patulous capsules in shoulder instability [7,12,15,21,28]. To date, however, the utility of the MRA as a tool to detect patulous hip capsules is unclear.…”
mentioning
confidence: 99%
“…Throughout the imaging the patient was positioned into a in a neutral position with the upper extremity in anatomical position. 6) Basic axial computed tomography (CT) imaging was taken in 16-sections or in 64-sections of either 2 or 3 mm thickness with a multi-detector CT.…”
Section: Imaging Techniquementioning
confidence: 99%
“…4,5) Shoulder instability has been shown to result by means of a large spectrum of pathological conditions such as labral deficiency, capsular elongation, patulousness of the shoulder capsule, ligament injury, bony defi-ciencies, and etc. [6][7][8] In 1962 Moseley 9) introduced a classification system based on the mode of capsular insertion for categorizing anatomical variations in the capsule that surrounds the glenohumeral joint. The three types of capsular insertion were as follows: type I, capsular insertion into the labral base; type II, capsular insertion into the glenoid fossa; and type III, capsular insertion into a more medial position following the scapular neck ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Stretching of the capsule and the posterior band of the inferior glenohumeral ligament beyond their initial resting length in this position has been shown to be a potential cause of both posterior shoulder instability and multidirectional instability 21,22 . Biomechanical studies have also shown that the posterior capsule and the posterior band of the inferior glenohumeral ligament may be permanently deformed as a result of repetitive lowstrain cyclic loading (e.g., repetitive microtrauma) and that recurrent posteroinferior subluxation of the humeral head can lead to plastic deformation of the capsule [23][24][25] .…”
Section: Dynamic Stabilizersmentioning
confidence: 99%